A case report of recessive myotonia congenita and early onset cognitive impairment: Is it a causal or casual link?. Issue 22 (June 2018) - Portaro, Simona; Cacciola, Alberto; Naro, Antonino; Milardi, Demetrio; Morabito, Rosa; Corallo, Francesco; Marino, Silvia; Bramanti, Alessia; Mazzon, Emanuela; Calabrò, Rocco Salvatore
Abstract: Rationale: Myotonia congenita (MC) is a non-dystrophic myotonia inherited either in dominant (Thomsen) or recessive (Becker) form. MC is due to an abnormal functioning of skeletal muscle voltage-gated chloride channel (CLCN1), but the genotype/phenotype correlation remains unclear. Patient concerns: A 48-year-old man, from consanguineous parents, presented with a fixed muscle weakness, muscle atrophy, and a cognitive impairment. Notably, his brother presented the same mutation but with a different phenotype, mainly involving cognitive function. Interventions: The patient was submitted to cognitive assessment, needle electromyography, brain and muscle MRI, and genetic analysis. Outcomes: The Milan Overall Dementia Assessment showed short-term memory, verbal fluency and verbal intelligence impairment. His genetic analysis showed a recessive splice-site mutation in the CLCN1 gene (IVS19+2T>A). Muscle MRI revealed a symmetric and bilateral fat infiltration of the tensor of fascia lata, gluteus medius, and gluteus maximus muscles, associated to mild atrophy. Diagnosis: Recessive myotonia congenita was diagnosed. Lessons: Further studies should establish if and to which extent the CLCN1 mutation is responsible for this c MC phenotype, taking into account a gene–gene and /or a gene–environment. Abstract : Supplemental Digital Content is available in the text